2019
DOI: 10.1186/s12862-019-1453-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of asexual Daphnia pulex in Japan: variations and covariations of the digestive, morphological and life history traits

Abstract: Background Several genetic lineages of obligate parthenogenetic Daphnia pulex , a common zooplankton species, have invaded Japan from North America. Among these, a lineage named JPN1 is thought to have started colonization as a single genotype several hundred to thousand years ago and subsequently produced many genotypes in Japan. To examine the phenotypic variations due to ecological drivers diverging the genotypes in new habitats, we measured heritability and variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 87 publications
(90 reference statements)
1
43
0
Order By: Relevance
“…For example, using 12 microsatellite loci, So et al (2015) detected only four MLGs in asexual Daphnia pulex that had invaded Japanese lakes and ponds. Interestingly, these MLGs comprised 21 mitochondrial haplotypes, indicating a higher genotype diversity than that resolved by the microsatellite loci (So et al, 2015), a finding that was later confirmed using whole-genome sequencing (Tian et al, 2019).…”
Section: Long-term Persistence Of Dominant Clonesmentioning
confidence: 74%
See 2 more Smart Citations
“…For example, using 12 microsatellite loci, So et al (2015) detected only four MLGs in asexual Daphnia pulex that had invaded Japanese lakes and ponds. Interestingly, these MLGs comprised 21 mitochondrial haplotypes, indicating a higher genotype diversity than that resolved by the microsatellite loci (So et al, 2015), a finding that was later confirmed using whole-genome sequencing (Tian et al, 2019).…”
Section: Long-term Persistence Of Dominant Clonesmentioning
confidence: 74%
“…Interestingly, these MLGs comprised 21 mitochondrial haplotypes, indicating a higher genotype diversity than that resolved by the microsatellite loci (So et al., 2015), a finding that was later confirmed using whole‐genome sequencing (Tian et al., 2019). In particular, these authors concluded that the observed divergent traits in these closely related asexual genotypes evolved without recombination from an ancestral clone by a limited number of functionally significant mutations (Tian et al., 2019). (iii) Epigenetic modifications explain clonal adaptation and allow clones to persist …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, using 12 microsatellite loci, So et al [61] detected only four MLGs in asexual Daphnia pulex that had invaded Japanese lakes and ponds. Interestingly, these MLGs comprised 21 mitochondrial haplotypes, indicating a higher genotype diversity than that resolved by the microsatellite loci [61], a finding that was later confirmed using whole genome sequencing [62]. In particular, these authors concluded that the observed divergent traits in these closely related asexual genotypes evolved without recombination from an ancestral clone by a limited number of functionally significant mutations [62].…”
Section: Long-term Persistence Of Dominant Clonesmentioning
confidence: 89%
“…Whole-genome sequencing was performed according to a previous study 60 . Fifty to seventy individuals of each genotype were collected for DNA extraction using a Maxwell (R) 16 instrument (Promega, Madison, WI, USA) and Maxwell (R) 16 LEV Plant DNA Kit (Promega).…”
Section: Methodsmentioning
confidence: 99%